2021
DOI: 10.3390/cancers13133267
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of KIR–HLA Pairs on Hepatocellular Carcinoma in Hepatitis C Virus Cirrhotic Patients

Abstract: Natural killer cells are partially mediated through the binding of killer cell immunoglobulin-like receptors (KIR) with human leukocyte antigen (HLA) class I ligands. This investigation examined the risk of hepatocellular carcinoma (HCC) in relation to KIR–HLA pairs in patients with compensated hepatitis C virus (HCV)-associated cirrhosis. A total of 211 Japanese compensated HCV cirrhotic cases were retrospectively enrolled. After KIR, HLA-A, HLA-Bw, and HLA-C typing, associations between HLA, KIR, and KIR–HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Many previous studies have shown that KIRs receptors, a group of Natural Killer receptors, play an important role in controlling the severity of viral diseases and infections in humans. 12,[23][24][25][26] Previous studies have already established a relationship between KIRs genes and certain infectious diseases and cancers, such as hepatitis B, 12,23,26 hepatitis C with hepatocellular carcinoma (27)(28)(29), and AIDS with Lymphomas. 11,24 The 20-39 year age group of patients had the highest frequency of dengue fever (64.00%) (table 1), and 90% (45/50) of patients had a secondary dengue infection in our population of the study (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have shown that KIRs receptors, a group of Natural Killer receptors, play an important role in controlling the severity of viral diseases and infections in humans. 12,[23][24][25][26] Previous studies have already established a relationship between KIRs genes and certain infectious diseases and cancers, such as hepatitis B, 12,23,26 hepatitis C with hepatocellular carcinoma (27)(28)(29), and AIDS with Lymphomas. 11,24 The 20-39 year age group of patients had the highest frequency of dengue fever (64.00%) (table 1), and 90% (45/50) of patients had a secondary dengue infection in our population of the study (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…10,18 KIR/HLA gene polymorphisms have been identified to be correlated with infections, autoimmune illnesses, and cancers. [19][20][21] 22,23 Recently, single nucleotide polymorphisms (SNPs) of KIR2DS4/KIR2DS1/KIR2DL1 and HLA-C have been linked to an elevated vulnerability to HCV infection in our previous study. 24 KIR2DL4 is referred to as one of the "framework" genes, which was detected 100% in random populations.…”
mentioning
confidence: 89%
“…KIR/HLA gene polymorphisms have been identified to be correlated with infections, autoimmune illnesses, and cancers 19–21 . Takeji et al found that KIR3DL1 + HLA‐Bw4 are associated with HCC development in HCV cirrhosis, and Zhengang et al found that KIR2DL5A−/2DL5B + associated with HCV spontaneous clearance 22,23 . Recently, single nucleotide polymorphisms (SNPs) of KIR2DS4/KIR2DS1/KIR2DL1 and HLA‐C have been linked to an elevated vulnerability to HCV infection in our previous study 24 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, specific interactions of classical HLA with innate lymphoid cells (ILC) receptors, such as those expressed by natural killer cell (NK) and ILC2, have been shown to be important activators of liver-disease-associated immune function [ 18 ]. Among them, several studies have associated class I HLA (mainly HLA-A-Bw4 and HLA-C) with NK cell KIR receptors and the response to interferon treatment to induce HCV and HBV viral clearance, as well as the risk of developing HCC [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Classical Hla Class I Molecules (Hla-ia)mentioning
confidence: 99%
“…Overall, HLA-F in open conformer by activation of NK cell function has been associated with the resolution of some infections, including HCV and HIV infection, while hemoglobin peptides had been proposed to have a role in HIV progression, due to a reduction of HLA-F/KIR3DS1 interaction [ 138 , 139 , 140 , 141 ]. Previous studies, including one of ours, when the HLA-F function of NKs was still unknown, highlighted the potential role of balance between KIR3DL1 and KIR3DS1 on NK function and outcomes of HCV, HBV and HCC [ 19 , 24 , 25 , 142 , 143 ]. Although the clinical relevance of HLA-F expression in HCC patients is still unclear, HLA-F has attracted attention as an important immunosuppressive molecule, the expression of which was found to correlate with the degree of lymphatic or venous invasion in HCC [ 144 ].…”
Section: Non-classical Hla Class I Molecules (Hla-ib)mentioning
confidence: 99%